Municipality-Level Source Apportionment of PM2.5 Concentrations based on the CAPSS 2016: (III) Jeollanamdo 2016년 국가배출목록 기반 지자체별 초미세먼지 기여도 분석: (III) 전라남도 - Kim, Soontae; You, Seunghee; Kim, Eunhye; Kang, Yoon Hee; Bae, Minah; Son, Kyuwon (Journal of Korean Society for Atmospheric Environment, 2021)
As a companion paper, in this study we analyzed the emission contributions, simulated with the Comprehensive Air quality Model with eXtensions with Particulate Source Apportionment Technology (CAMx-PSAT), to PM2.5 concentrations in twenty-two local authorities in Jeonnam for the year of 2016. The foreign contribution estimated with the CREATE 2015 to the annual mean PM2.5 in Jeonnam was lower than those to Incheon, Seoul, and Jeonbuk by 26%, 19%, and 5%, respectively, and higher than those to Ulsan and Busan by 29% and 28%. The difference from the relative foreign contribution averaged over the local authorities varied from -10% to +10% (-2~+2 μg/m3). The domestic and the provincial self-contributions, estimated with the Clean Air Policy Support System 2016 emissions inventory, to the annual PM2.5 concentrations in Jeonnam was 6.9 (3.6~13.2), and 3.7 (1.7~9.6) μg/m3, respectively. Note that those were relatively lowered over the coastal and island areas, especially for the local authorities in the west coast. It is, therefore, important to deliberate the air quality management plan in Jeonnam to improve PM2.5 concentrations including those blind spots. Inter-provincial PM2.5 contributions appeared to be as significant as the intra-provincial contributions for the local authorities. For example, local authorities located in northern Jeonnam encountered the annual mean contributions from Jeonbuk and Chungnam as high as 1.8 μg/m3 (Jangseong), and 1.4 μg/m3 (Yeonggwang), respectively. On the other hand, emissions from Gyeongnam increased the annual mean PM2.5 concentrations in Gwangyang by 1.2 μg/m3. The averaged PM2.5 self-contributions for the twenty-two local authorities was 1.5 μg/m3 which was lower than the contributions from the rest of Jeonnam (2.2 μg/m3). However, uncertainties in the emissions inventory used in this study have clearly led to the over-predictions of the contributions in some monitoring sites, which should be corrected to better understand the source-receptor relationship in Jeonnam.
Keywords: Coast and islands; Contributions; Emissions; Jeonnam; PM2.5